ANALISA HUKUM TERHADAP KECELAKAAN LALU LINTAS YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG LAIN YANG DI LAKUKAN OLEH ORANG KARENA PENGARUH MINUMAN KERAS (Studi Kasus Putusan Nomor : 92/Pid.B/2011/PN.kdl) - Agus Supriyadi; Anis Mashdurohatun (Jurnal Hukum Khaira Ummah, 2017)
This paper discusses Legal analysis of traffic accidents which result in loss of life of other people who do by people because of the influence of liquor (Case Study Decision Number: 92 / Pid.B / 2011 / PN.kdl)The impact of drinking liquor if viewed in terms of health if excessive will have a negative impact on health and if viewed from the social side, the habit of drinking this liquor cause many problems, such as irritability, discomfort of people who live in the vicinity, and the cause of the accident traffic. In addition, liquor is also usually the cause of violence in the household.The panel of judges who examines, judges and decides this case has applied the applicable law in accordance with applicable criminal law. This can be shown by seeing that the judges in deciding that the defendant's actions fulfilled the elements of traffic negligence in accordance with Article 310 Paragraph (4) of RI Law no. 22 of 2009 on Road Traffic and Transportation, based on material truths obtained from the indictment, witness statements, facts and evidences revealed in the proceedings.The judge's legal considerations in Decision Number 92 / Pid.B / 2011 / PN.kdl, based on the facts that arise in the court, judge that the defendant can be held accountable for the deed done with the consideration that at the time of his act the defendant is aware of the consequences, In doing his actions are in a healthy condition and capable to consider his actions. There are elements against the law, and there is no reason for criminal abolition. Keywords: Traffic Accident, Loss of Life